Upaya Pengendalian Banjir Kawasan Sub-Das Celeng Pra Pembangunan Embung Imogiri - Fadila, Shofwatul; Purboseno, Sentot (Rifa'Institute, 2022)
Flood on March 17 in the Celeng River, Wukirsari Village, D.I. Yogyakarta became the biggest flood that ever happened on the Bog River. Floods are caused by heavy flow of water from the hills in the Imogiri and Dlingo areas. The Celeng River overflowed and submerged four hamlets in Wukirsari Village, Imogiri District. This study aims to determine flood control efforts in the Celeng sub-watershed area. The research location is in the Kali Celeng sub-watershed, Wukirsari, Imogiri, D.I. Yogyakarta with the control point located in the lower reaches of the Celeng River right at the confluence of the Celeng River and the Oyo River. The hydrological analysis was calculated using the Gamma 1 unit hydrograph method with a return period of 10 years. The maximum flood discharges for each of the Celeng sub-watersheds are 75.73 m3/s, 38.22 m3/s, 37.20 m3/s, 18.54 m3/s, and 21.57 m3/s, and 26.29 m3/s, while the 10-year return flood discharges for the Oyo watershed is 959.60 m3/s. The hydraulic analysis was carried out by modeling the 13.35 km long Celeng River channel with HEC-RAS 4.1 software. The flow simulation is carried out steadily. The simulation results show that during the simulation of the existing state there are several points of the section of the Celeng River that overflow. The overflowing sections are then normalized with certain groove dimensions that are adjusted to the location of the flood point. The results of the flow simulation after normalization show that most of the Celeng River channel can accommodate the flood discharge that occurred. The sections that still overflow after normalization are then given embankments with an average height of 0.75 m.